Human adipose tissue‐derived tenomodulin positive subpopulation of stem cells: A promising source of tendon progenitor cells. (4th October 2017) - Gonçalves, A.I.; Gershovich, P.M.; Rodrigues, M.T.; Reis, R.L.; Gomes, M.E.
Abstract: Cell‐based therapies are of particular interest for tendon and ligament regeneration given the low regenerative potential of these tissues. Adipose tissue is an abundant source of stem cells, which may be employed for the healing of tendon lesions. However, human adult multipotent adipose‐derived stem cells (hASCs) isolated from the stromal vascular fraction of adipose tissue originate highly heterogeneous cell populations that hinder their use in specific tissue‐oriented applications. In this study, distinct subpopulations of hASCs were immunomagnetic separated and their tenogenic differentiation capacity evaluated in the presence of several growth factors (GFs), namely endothelial GF, basic‐fibroblast GF, transforming GF‐β1 and platelet‐derived GF‐BB, which are well‐known regulators of tendon development, growth and healing. Among the screened hASCs subpopulations, tenomodulin‐positive cells were shown to be more promising for tenogenic applications and therefore this subpopulation was further studied, assessing tendon‐related markers (scleraxis, tenomodulin, tenascin C and decorin) both at gene and protein level. Additionally, the ability for depositing collagen type I and III forming extracellular matrix structures were weekly assessed up to 28 days. The results obtained indicated that tenomodulin‐positive cells exhibit phenotypical features of tendon progenitor cells and can be biochemically induced towards tenogenic lineage, demonstrating that this subset of hASCs can provide a reliable source of progenitor cells for therapies targeting tendon regeneration.